Außergerichtliche Konﬂiktlösung in der Antike Beispiele aus drei Jahrtausenden - Pfeifer, Guido; Grotkamp, Nadine (Global Perspectives on Legal History, 2017)
"Antiquity is often utilized as a reference to provide a historical dimension for contemporary phenomena. This also holds true for the prevailing scientific discourse on alternative or adequate remedies of dispute resolution. In this context, historical perspectives seem to be in vogue as narratives to legitimize one or another role model, whereas studies on practical examples from ancient legal orders tend not to be given serious consideration in the current debate. Just as in the case of contemporary legal research, ancient legal history also distinguishes litigation at court from other mechanisms of conflict resolution. Nevertheless, where do the boundaries of judicial and extra-judicial mechanisms of dispute resolution lie within the framework of ancient societies? Are they alternatives in a narrower sense? Is there evidence for concerning the reason there was no (or at least no exclusive) judicial decision? This volume offers a selection of studies of pertinent illustrative material pertaining to these questions. While the relevant sources stemming from the prehistorical period, the Ancient Near East, Hellenistic Egypt and Classical Roman law may vary greatly, this just serves to widen our perspective on ancient times. Heidi Peter-Röcher focuses on strategies of conflict resolution in prehistoric times corresponding to different forms of violence. Hans Neumann, Susanne Paulus, Lena Fijałkowska and Alessandro Hirata delve into case studies situated in the Ancient Near East from Sumerian to Neo-Babylonian times. Three other contributions examine Graeco-Roman Antiquity: Marc Depauw considers non-Greek, i.e., demotic, material from a Hellenistic kingdom, Anna Seelentag embraces the phenomenon of public clamour in the Roman Republic, and Christine Lehne-Gstreinthaler provides a fresh look at the classical arbitration from the perspective of ancient legal history."